Revealing In Silico that Bacteria’s Outer Membrane Proteins may Help our Bodies Replicate and Carry Severe Acute Respiratory Syndrome Coronavirus 2 - Emre Aktaş; Nehir Özdemir Özgentürk (Bioinformatics and Biology Insights, 2022)
Some studies in the literature show that viruses can affect bacteria directly or indirectly, and viruses use their own specific ways to do these interactions. Furthermore, it is said that bacteria are prone to attachment mammalian cells during a viral illness using their surface proteins that bind to host extracellular matrix proteins such as fibronectin, fibrinogen, vitronectin, and elastin. A recent study identified the cooperation between bacteria and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in silico, in vitro, and in vivo. Like this study, we hypothesized that more bacteria protein might help SARS-CoV-2 transport and attach to angiotensin-converting enzyme 2 (ACE2). The bacteria’s outer membrane proteins (OMPs) we chose were not random; they had to be on the outer surface of the bacteria because these proteins on the outer surface should have a high probability of interacting with both the spike protein and ACE2. We obtained by using bioinformatics tools that there may be binding between both ACE2 and spike protein of these bacteria’s OMPs. Protein-protein interaction results also supported our hypothesis. Therefore, based on our predicted results, these bacteria OMPs may help SARS-CoV-2 move in our body, and both find and attach to ACE2. It is expected that these inferences obtained from the bioinformatics results may play a role in the SARS-CoV-2 virus reaching host cells. Thus, it may bring a different perspective to studies on how the virus can infect host cells.